Отпетые любовники - Колычев Владимир Григорьевич (Колычев, 2015)
Экземпляры: АБ (20150923) / Инвентарный номер: 59650 / Цена: 183.00 / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: К 61 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44